(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the various ocular manifestations in xeroderma pigmentosum seen at Eye and Dermatology Department of Chandka Medical College Hospital Larkana. Study Design: Prospective study Place and Duration of Study: This study was carried out at two Departments, i.e. at Departments of Dermatology and Ophthalmology of Chandka Medical College larkana from January 2013 to December 2014. Material and methods: Twenty cases were enrolled from outpatient of Eye and Skin Department, Chandka Medical College Hospital Larkana. Patients were subjected to detail history, complete eye and skin examination and relevant investigations. Results: 20 patients, 12(60%) males and 8 (40%) females with xeroderma pigmentosum in a gender ratio of 1.5 : 1 were recruited. All patients had skin freckles and increased sensitivity to sun light. Photophobia and conjunctivitis was seen in 18(90%) cases, keratitis and dry eyes was seen in 12 (60%) cases and 4 (20%) cases had malignancies of lids and conjunctiva proved on biopsy. Our cases belongs to larkana and sukkur division. Conclusion: The present study highlights the eye involvement in xeroderma pigmentosum and thereby early detection of eye disease prevent the malignancies and blindness